Controlled Morphology of Silica Particle by Spray Drying Method - Albar, Abdurrahman Anis; Widiyastuti, Widiyastuti; Setyawan, Heru (IPTEK Journal of Proceedings Series, 2020)
The controlled morphology of mesoporous silica particle with colloidal silica as precursor solution was investigated using spray drying method. The colloidal silica solution was made from sodium silicate (waterglass) using sol-gel method. The operating condition of spray dring such as precursor solution volumetric rate and hot air flowrate was varied to study the effect of the silica particle’s morphology. Two-fluid nozzle was used as atomizer with volumetric rate ranged from 1.6 mL/min to 5 mL/min, and hot air heated from tubular furnace with flowrate ranged from 210 L/min to 414 L/min, both resulting doughnut-like shape with more doughnut fraction with increased volumetric rate. With the increase of volumetric rate from 1.6 mL/min to 5 mL/min, the surface area and total pore volume are tend to decrease (168.234 to 131.001 m2/g and 0.1652 to 0.1251 cc/g respectively). Meanwhile, for increasing hot air flowrate from 210 L/min to 414 L/min, the surface area are tend to increase (135.353 to 168.234 m2/g) but total pore volume tend to decrease (0.1921 to 0.1652 cc/g).